One Night in Miami... [videorecording (DVD)] - Odom, Leslie, Jr., 1981-; Hodge, Aldis; Ben-Adir, Kingsley; Goree, Eli; Reddick, Lance; Imperioli, Michael, 1966-; Gilliard, Larry; Bridges, Beau (Criterion collection., 2021)
A fictional account of one amazing night where icons Muhammad Ali, Malcolm X, Sam Cooke, and Jim Brown gathered discussing their roles in the Civil Rights Movement and cultural turmoil of the '60s.